Dispositional Self-Construal Modulates Neural Representation of Self: An ERP Study - Jie Chen; Jie Chen; Panpan Yuan; Panpan Yuan; Yaohan Cai; Yaohan Cai; Cuihong Liu; Cuihong Liu; Wenjie Li; Wenjie Li (Frontiers in Psychology, 2020)
This study aimed to investigate the influence of dispositional self-construal on self-related processing. Event-related potentials (ERPs) were recorded for a participant’s own and a famous person’s name in a three-stimulus oddball task. The results showed greater P2 and P3 amplitudes induced by one’s own than by a famous person’s name in both independent and interdependent self-construal groups. However, no N2 amplitude differences were found between the partcipant’s own name and a famous person’s name in either group. Moreover, the strength of the P2 effect (own vs. famous person’s name) was stronger in the independent than in the interdependent self-construal group, whereas the P3 effect was similar between these two groups. Thus, these findings might reflect fast modulation of self-related processing by dispositional self-construal.